Mental illness through the perspective of undergraduate medical students in Greece: a cross-sectional study at Aristotle University of Thessaloniki - Porfyri, Georgia-Nektaria; Athanasiadou, Maria; Siokas, Vasileios; Angelopoulos, Konstantinos; Skarpari, Sofia; Zagalioti, Sofia-Chrysovalantou; Dardiotis, Efthimios; Rudolf, Jobst; Deretzi, Georgia; Konsta, Anastasia; Diakogiannis, Ioannis (Frontiers in Psychiatry, 2023)
Numerous studies reveal that mental health-related stigma, stereotypes, and prejudices negatively affect the patients, jeopardizing their health, prognosis, and social opportunities. Healthcare professionals, who are in the first line of combating mental disease, are expected to play a significant role in drastically changing discriminatory and stigmatizing attitudes towards psychiatric patients. In this study, we aimed to explore and highlight the views of Greek medical students towards mental illness and people suffering from it. It is a cross-sectional, observational study, in which 324 undergraduate students from the most populous Greek medical school of the Aristotle University of Thessaloniki, participated online, during the spring semester of 2022. The tools used were the Opinions about Mental Illness Scale (OMI) that assesses one’s viewpoints about mental illness, the Social Distance Scale (SDS) that captures the desired degree of social distancing from patients with mental disorders, and the Level of Contact Report (LCR-12) that estimates the level of familiarity with them. Participants displayed rather positive attitudes regarding the etiology of mental illness, social integration and discrimination towards psychiatric patients, and more clearly favorable opinions concerning the need for social provision or the enactment of restrictive measures, while claiming to be quite familiar with mental disorders and individuals experiencing them, and relatively willing to interact with them. Degree of familiarity with mental illness was directly proportional to the desire for contact with patients living with it, while the higher both were, the more improved most of the aforementioned OMI sectors were found to be. Female sex, clinical medical education, previous clinical psychiatric training, and living with or being a person with a mental disorder were the factors that defined a statistically refined profile in many of the aspects above. Our findings are in accordance with many prior studies, while showing improved opinions compared to those of previous research in Greek student and healthcare population. They are calling for vigilance, rather than complacency, as well as educational and social interventions, in order to enable current and future healthcare professionals to perform their function to its fullest extent. Implications of our results and further research suggestions are included.